CREATION OF INTERACTIVE MULTIMEDIA BASED ON THE DOUBLE LOOP PROBLEM SOLVING MODEL TO IMPROVE STUDENTS' PROBLEM-SOLVING SKILLS ON DYNAMIC FLUID MATERIALS - Devitayanti, Zahra (PILLAR OF PHYSICS EDUCATION, 2024)
The development of Interactive Multimedia based on the Double Loop Problem Solving model utilizes iSpring Suite software which is intended to provide one of the answers to learning media that does not support learning in schools. This research aims to produce Interactive Multimedia that is valid and practical to use in improving students' problem-solving skills with F1 phase research subjects. The 4D development model consists of 4 stages, namely Define, Design, Development, and Disseminate. The assessment instrument consists of two, namely the validity instrument of content/material and media and the instrument of practicality. The data in this study are needs analysis data, validity data, and practicality data. The data obtained were analyzed using the Aiken's V formula and the Likert Scale. Based on the analysis of validity data, a validity score with an average of 0.81, 0,78, 0,80, and 0,86 was obtained with a valid category. The analysis of teacher and student practicality data was obtained on average 97%, 96,5%, 92.4%, and 91,3% with the practical category.  Therefore, it can be concluded that interactive multimedia based on the Double Loop Problem Solving model developed is valid and practical.